An Electrochemical Impedance Study of AISI 321 Stainless Steel in 0.5 M H2SO4 - A. Fattah-Alhosseini; M. Mosavi; A. Allahdadi (International Journal of Electrochemistry)
The electrochemical behavior of passive films formed on AISI 321 has been examined using electrochemical impedance spectroscopy. AISI 321 is characterized by high interfacial impedance, thereby illustrating its high corrosion resistance. Results showed that the interfacial impedance and the polarization resistance initially increase with applied potential, within the low potential. However, at a sufficiently high potential (𝐸>0.6 V), the interfacial impedance and the polarization resistance decrease with increasing potential. The impedance data were adequately represented by an equivalent electrical circuit model based on point defect model, which described the behavior of the passive film on stainless steel more satisfactorily than the proposed models.